The Effect of Implementing Green Accounting on Company Financial Performance - Wulandari, Ayu Lus; Rastafael, Yoel; Hwihanus, Hwihanus (CV. Lenggogeni Data Publishing, 2024)
In industrial competition, obtaining maximum profits is a company goal, so that in this increasingly hot competition all companies are competing and fighting to be able to improve their company's performance, increasing company performance can help maintain making industry players try to improve their performance in order to maintain the company's life in the future as well as able to compete optimally. However, companies sometimes do not think about the consequences of the company's production process on the environment. This research uses the Meta Analysis method which was carried out on several international articles and journals. This meta-analysis research is a method used to analyze and combine several existing studies to obtain new findings and obtain general conclusions from these studies. Based on research on several existing studies, it can be concluded that green accounting can be useful, because it can improve company performance. Green accounting used in companies can help achieve business goals, because green accounting can help management find out whether the company is able to carry out its obligations or responsibilities towards sustainable development.